The Influence of Communication, Leadership, Work Discipline, and Work Culture on Employee Performance and Organizational Commitment - Ririn Yulianti; Joko Utomo; Mulyanto Mulyanto (GLOBAL HEALTH SCIENCE GROUP, 2026)
In today’s dynamic and competitive organizational environment, employee performance and organizational commitment are critical factors that determine organizational sustainability and competitiveness. Effective communication, strong leadership, high work discipline, and a supportive work culture are considered fundamental elements that can enhance employee attitudes and behaviors in achieving organizational goals. However, the extent to which these factors simultaneously influence employee performance and organizational commitment requires empirical investigation. This study aims to analyze the influence of communication, leadership, work discipline, and work culture on employee performance and organizational commitment. The research employed a quantitative approach with a sample of 186 respondents. The sampling technique used purposive sampling. Primary data were collected using structured questionnaires distributed to employees. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS software to examine both direct and indirect relationships among variables. The results indicate that communication, leadership, work discipline, and work culture have a positive and significant effect on employee performance. Furthermore, communication, leadership, work discipline, and work culture also have a positive and significant effect on organizational commitment. In addition, organizational commitment is proven to have a positive and significant effect on employee performance.